Nonstationary resonant dynamics of oscillatory chains and nanostructures. ([2018]) - Manevich, L. I (Leonid Isaakovich); Kovaleva, A. S (Agnesa Solomonovna); Smirnov, Valeri; Starosvetsky, Yuli, 1978-
No abstract available